1993
DOI: 10.1111/j.1469-8986.1993.tb01730.x
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring retrieval from long‐term memory by slow event‐related brain potentials

Abstract: Slow event-related brain potentials of nine subjects were recorded in an experimentally controlled long-term memory retrieval task (the Fan paradigm) from electrode sites F3, Fz, F4, Cz, P3, Pz, and P4. In all retrieval conditions, a very pronounced DC-like negative potential appeared over the left frontal cortex. This negativity was switched on with the presentation of the probe stimuli and prevailed in some conditions throughout the total recording epoch of 14 s. Particular retrieval conditions became manife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(36 citation statements)
references
References 31 publications
5
31
0
Order By: Relevance
“…This explanation is supported by Baggio et al (2008), who also found a sustained negativity when a default inference had to be overridden and revised, albeit that the scalp distribution of the observed effect in our study was more central than in their study. Alternatively, the sustained negativity may reflect an attempt to link the exception with information retrieved from long-term memory, or extra working memory demands to hold information about the exception in mind in order to withdraw the conclusion (Markovits & Potvin, 2001;Vadeboncoeur & Markovits, 1999;Rösler, Heil, & Glowalla, 1993). However, the working memory account seems less likely because we failed to find any relationship between reading span and suppression, and between reading span and the ERP effect.…”
Section: Discussionmentioning
confidence: 78%
“…This explanation is supported by Baggio et al (2008), who also found a sustained negativity when a default inference had to be overridden and revised, albeit that the scalp distribution of the observed effect in our study was more central than in their study. Alternatively, the sustained negativity may reflect an attempt to link the exception with information retrieved from long-term memory, or extra working memory demands to hold information about the exception in mind in order to withdraw the conclusion (Markovits & Potvin, 2001;Vadeboncoeur & Markovits, 1999;Rösler, Heil, & Glowalla, 1993). However, the working memory account seems less likely because we failed to find any relationship between reading span and suppression, and between reading span and the ERP effect.…”
Section: Discussionmentioning
confidence: 78%
“…We also explicitly tested for the topographical di erences between the ®rst and second P600/SPS latency window. This was done after rescaling the e ect sizes in the two windows as z-scores such that for each window means and variances across electrode sites became 0 and 1, respectively [31]. This procedure is equivalent to the procedure suggested by McCarthy and Wood [19].…”
Section: Resultsmentioning
confidence: 99%
“…To some extent, a similar pattern was seen in previous w x w x work with visual sentences 15 and word pairs 17 ; negativities with a similar distribution but of shorter duration than these slow potentials were seen for moderate w x working memory loads by Ruchkin et al 32 . More w x recently, Rosler et al 30 have used ERPs to investigatë the fan effect and have shown very robust left anterior negativities related to the active retrieval and evaluation of information in these paradigms; moreover, the size of this frontal negativity increases with the difficulty of the comparison being made. Thus, more work will have to be done with both visual and auditory sentences, however, before we can be certain exactly what aspect of the processes involved are indexed by these slow potentials.…”
Section: Discussionmentioning
confidence: 99%